Micron-sized iron-oxide secondary particles as anode material for high volumetric-energy-density of lithium-ion batteries. (March 2018) - Xu, Xiaoqian; Wan, Yuanxin; Zuo, Chen; Yan, Haipeng; Du, Muting; Xue, Gi; Zhou, Dongshan
Abstract: Low volumetric-energy-density caused by low tap density of nanomaterial seriously restricts the application of nanomaterial in lithium-ion batteries. Here, to solve this problem, micron-sized Fe2 O3 secondary particles (MFSPs) with high tap density (2.8 g cm −3 ) are synthesized via a facile way. As a result, ultrahigh volumetric-energy-density of 1490 mA h cm −3 is obtained after 100 cycles at C/2 (∼500 mA g −1 ). Densely packed structure of MFSPs exhibits well structural stability and electrical conductivity. For the high areal mass loading of 4.02 mg cm −2, an areal capacity about 3 mA h cm −2 is achieved. Graphical abstract: Highlights: Micron-sized Fe2 O3 secondary particles (MFSPs) with uniform size (6 μm) are synthesized via a facile way. High volumetric-energy-density and areal-energy-density of MFSPs is obtained due to its high tap density. The first work to discuss the volumetric-energy-density and areal-energy-density of Fe2 O3 .